Corruption in folk customs in Serbia – socio-ethnological approach - Joković, Milica (Sociološki pregled, 2022)
The paper analyzes corruption in the framework of folk customs in Serbia from the socio-ethnological aspect. The analysis includes manners and forms of corruption generated and practised in the last period of the Ottoman Empire rule in Serbia. Through the records of the most eminent students of Jovan Cvijić, first Serbian great scientist, it is shown how corruption emerged and developed in Serbia and how it affected Serbian people’s folk customs. The analysis covers research ventures showing the manners, forms and types of corruption practised in Serbia at the time of formation the new-century Serbian statehood in the 19th century, as well as at the beginning of the 20th century and between two world wars. Typologically speaking, corruption in Serbia belongs to parochial, institutional and political corruption. The paper particularly analyzes disapproval and justification of corruption in the Serbian national tradition. In the conclusion of the paper, it is emphasized that socio-ethnological records show that corruption and/or bribe emerged as a consequence of people’s greediness, but also of unfavourable historical and social circumstances leading to the negative experience and negative patterns of corruptive behaviour. This was crystallized in the form of messages passed from one generation to another.
Keywords: corruption; folk customs; parochial corruption; institutional corruption; political corruption